Cyber Warfare and National Security - Khoirunnisa Khoirunnisa; Indrawati; Ambarwati; Yanuar Rahmadan; Didi Jubaidi (China Quarterly of International Strategic Studies)
This study aims to provide insights into cyber threats as a new form of conflict, their regulation under international law, and the potential measures that nations, particularly China, can adopt to mitigate their harmful consequences. The main research question is what challenges nations face in developing an effective international legal framework to address growing cyber threats. Employing a normative approach, the study integrates conceptual and legal analyses to answer the question. Content analysis is utilized to elaborate on the research findings. The results emphasize the importance of establishing a shared understanding of cyber threats, which are increasingly recognized by the global community as a distinct form of conflict. China’s active role in cyber operations highlights the complexities of international responses to such threats, as it often engages in cyber activities that challenge existing norms and regulations. Additionally, the study highlights the need for consistent international regulation of cyber threats, given the influence of major cyber powers like China on global cyber governance. Furthermore, the study emphasizes the significance of conducting regular cyber defense exercises, leveraging artificial intelligence to reduce the impact of cyberattacks, and fostering greater international cooperation, particularly in addressing the challenges posed by state actors. The necessity of developing a universally accepted definition of cyber threats and achieving international consensus on their interpretation within the context of international law is underscored, especially as differing perspectives, such as those from China and Western nations, complicate these discussions.